The availability of teaching requirements in computer laboratories in government schools in Al Balqa governorate from the point of view of technicians and specialized teachers - Al Hamadeen, Hind Mousa (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal the availability of teaching requirements in computer laboratories in government schools in Al Balqa governorate from the point of view of technicians and specialized teachers. The descriptive analytical method was used through a questionnaire consisting of (25) paragraphs and distributed into (4) dimensions. The tool was applied to a component sample Of (120) computer teachers and technicians, including (78) teachers and 42 technicians in government schools in Balqa Governorate, during the first semester of the year (2019- 2020), the results showed that the total degree of teaching requirements in computer labs from the point of view of technicians and specialized teachers obtained a total average (3.42 out of 5) with a percentage of M. Priority (68.4%), and In terms of dimensions; computers and their accessories got the highest arithmetic average (3.73) and a percentage(74.6%), followed by the school administration dimension with an average arithmetic (3.55) and a percentage(71%), then the curriculum dimension with an average arithmetic (3.05) and a percentage(61%), and fina The results showed that there were statistically significant differences on the total score for the responses of the study sample according to the variable of the academic qualification, and for the benefit of the diploma holder, while there were no statistically significant differences on the total score for the responses of the study sample according to the gender variable or the variable of years of experience or the variable number of training courses. In light of the results, a number of recommendations and proposals were presented, including: Holding the necessary training programs for computer teachers and technicians in the field of maintenance and networks to ensure that they are provided with the required skills and capabilities that will improve their performance and in line with the software and developed curricula such as courses((CISCO CCNA ,A+) , Increasing the number of classes for the practical application of the computer curriculum inside the computer lab, in addition to directing the school administration towards allocating an adequate budget for the computer lab to ensure the longevity of the laboratory’s work.